American Pastoral's crisis of humanism: hands, gloves and one colossal Turkey*. Issue 9 (21st October 2019) - Bagon, Robin
ABSTRACT: This paper argues that, contrary to the accepted critical discourse on Philip Roth, his novel American Pastoral (1997) contains a powerful critique of traditional humanism. This operates both explicitly and implicitly throughout the novel. In a manner which is frequently foregrounded, Zuckerman, the narrator, revels in exposing the pitiful limits of rationalism. Both the structure and overt content of the novel highlight the inadequacies of rational thought, something which is fundamental to the post-Enlightenment understanding of the human as the rational animal and which underpins the Cartesian understanding of the human. In a less obvious manner, alongside this unravelling of traditional beliefs about the human, we find that Roth exposes the operations of what Jacques Derrida calls carnophallogocentrism, part of which describes how the human is secured through the death of the nonhuman animal. This is seen, perhaps most strikingly, in Roth's presentation of the Thanksgiving turkey. Additionally, Roth's focus on the manufacture of leather gloves aptly articulates a set of meanings involving human hands and dead sheep which strikingly engages with and concurs with Derrida's criticism of Martin Heidegger's thinking on the human.